(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
The relevance of this study is обусловлена высокой частотой сочетания bronchial asthma (BA) and type 2 diabetes mellitus (T2DM), which mutually aggravate the clinical course. The aim of the study was to investigate clinical and immunobiochemical markers to improve diagnosis and assess disease severity. A total of 42 patients were examined and divided into two groups: isolated BA and BA combined with T2DM, with comprehensive clinical, laboratory, and immunological assessments performed. An increase in IL-4 levels up to 30.1 ± 1.4 pg/mL in BA+T2DM compared to BA (24.7 ± 1.2 pg/mL) and a decrease in IFN-γ to 12.3 ± 0.8 pg/mL relative to the control group (18.3 ± 1.0 pg/mL; p < 0.05) were observed. Endothelin-1 concentration increased to 2.41 ± 0.12 pg/mL alongside elevated HbA1c levels up to 8.44 ± 0.91%, reflecting endothelial dysfunction and metabolic disturbances. The level of sRAGE decreased to 720.5 ± 150.4 pg/mL in the comorbid group compared to BA (980.3 ± 180.1 pg/mL) and control (1450.3 ± 210.3 pg/mL; p < 0.05), indicating enhanced oxidative stress. The obtained results confirm the activation of inflammatory and metabolic pathways in BA combined with T2DM and justify the need for comprehensive laboratory monitoring.